High-Resolution Infrared Spectroscopy of DC3N in the Stretching Region - Jiang, Ningjing; Melosso, Mattia; Tamassia, Filippo; Bizzocchi, Luca; Dore, Luca; Canè, Elisabetta; Fedele, Davide; Guillemin, Jean-Claude; Puzzarini, Cristina (Frontiers in Astronomy and Space Sciences, 2021)
The perspectives opened by modern ground-based infrared facilities and the forthcoming James3Webb Telescope mission have brought a great attention to the ro-vibrational spectra of simple interstellar molecules. In this view, and because of the lack of accurate spectroscopic data, we have investigated the infrared spectrum of deuterated cyanoacetylene (DC3N), a relevant astrochemical species. The nu1, nu2, and nu3 fundamentals as well as their hot-bands were observed in the stretching region (1 500–3 500 cm−1) by means of a Fourier transform infrared spectrometer. Supplementary measurements were performed at millimeter-wavelengths (243–295 GHz) with a frequency-modulation spectrometer equipped with a furnace, that allowed to probe pure rotational transitions in the investigated stretching states. Furthermore, since HC3N is observed as by-product in our spectra and suffers from the same deficiency of accurate infrared data, its ro-vibrational features have been analyzed as well. The combined analysis of both rotational and ro-vibrational data allowed us to determine precise spectroscopic constants that can be used to model the infrared spectra of DC3N and HC3N. The importance of accurate molecular data for the correct modeling of proto-planetary disks and exoplanetary atmospheres is then discussed.